Tuberculosis in Children and Adolescents: Progress and Perseverance - Graham, Stephen M.; Marais, Ben J.; Amanullah, Farhana (Pathogens (Basel), 2022)
Although it is an ancient pathogen, tuberculosis (TB) remains a major infectious cause of death globally, transiently displaced by COVID-19 [...].Although it is an ancient pathogen, tuberculosis (TB) remains a major infectious cause of death globally, transiently displaced by COVID-19 [...].